Analisis Penerimaan Electronic Money bagi Mahasiswa Kota Batam dengan Model Tam: Studi Kasus pada Link Aja - Suwarno Liang; Violin Anjeli Anggraini (Departement of Mathematics Education, 2023)
Electronic money is one example of the development of digital technology. One example of electronic money in Indonesia is Link Aja. However, the use of the Link application is still rare, especially among students. This research aims to analyze the acceptance of electronic money for Batam city students. This research is descriptive research with a quantitative approach. The model used to analyze acceptance of electronic money in this study is TAM which consists of perceived ease of use, perceived usefulness, perceived trust and perceived risk. The population in this study were students at 5 tertiary institutions in Batam City, namely 7,226, while the sample used was 100 students in 5 tertiary institutions in Batam City. Data collection in this study used a questionnaire made via Google Form media and will be distributed via social media such as Line, Whatsapp, Instagram. The data obtained will be analyzed using SPSS software. The results showed that the variables perceived convenience, perceived trust, and perceived satisfaction had a significant effect on students' interest in using LinkAja. While the perception of benefits has no significant effect on the user loyalty variable.